Mycoremediation effect of Trichoderma harzianum strain T22 combined with ozonation in diesel-contaminated sand. (August 2020) - Elshafie, H.S.; Camele, I.; Sofo, A.; Mazzone, G.; Caivano, M.; Masi, S.; Caniani, D.
Abstract: This study aimed to determine the ability of the fungus Trichoderma harzianum strain T22 ( Th -T22) to utilize diesel fuel as a carbon source. The potential use of Th -T22 for diesel bioremediation in an artificial soil was tested by inoculating a diesel-sand mixture with a fungal mycelial suspension of Th -T22. Given the ability of ozone to degrade compounds with low biochemical reactivity, the effect of a pre- and post-ozonation was also evaluated. The survival, growth and sporulation of Th -T22 throughout the bioremediation trial were monitored in all the treatments. In the post-ozonation treatments, the biodegradation percentages of diesel removal were 70.16% and 88.35% in Th -T22-inoculated sand treated or untreated with the antibacterial streptomycin, respectively. The results showed that ozonation alone caused good removal efficiencies (41.9%) but it was much more effective if combined with Th -T22 in a post-ozonation regime, whereas pre-ozonation negatively affected the subsequent biodegradation, likely due to its disinfectant and oxidizing effect on Th -T22. The results obtained demonstrated the significant mycoremediation ability of Th -T22 in diesel-contaminated sand and its possible use as a bioremediation agent for diesel spills in polluted sites. Graphical abstract: Image 1 Highlights: Bioremediation by Trichoderma harzianum in diesel-contaminated sand was studied. The effect of ozonation was also examined (pre- and post-treatment). Survival, growth and sporulation of T. harzianum were monitored. T. harzianum showed mycoremediation effect in diesel-contaminated sand. Pre-ozonation negatively affected the subsequent biodegradation.